2011
DOI: 10.2135/cropsci2010.04.0204
|View full text |Cite
|
Sign up to set email alerts
|

Rumen‐Undegradable Protein Supplementation Effects on Early Weaned Calves Grazing Annual Ryegrass

Abstract: Early weaned beef calves (Bos spp.) can be raised on cool‐season pastures in Florida but more information on protein supplementation is necessary to optimize the performance of those calves. The objective of this study was to evaluate the effects of three levels of rumen‐undegradable protein (RUP) supplementation on performance of early weaned calves grazing annual ryegrass (Lolium multiflorum Lam.) pastures. The study was conducted in Ona, FL in 2007 and 2008. Treatments were 1.5 g kg−1 body weight (BW) suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Supplementation may alter grazing behavior and forage intake, which affects forage growth and appearance of new tissues with greater nutritive value. Vendramini et al (2011) observed that annual ryegrass pastures grazed by early weaned calves receiving greater levels of RUP had greater HM and HA. The greater HM and HA observed was attributed to decreased FDMI of the calves receiving greater RUP supplementation levels.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Supplementation may alter grazing behavior and forage intake, which affects forage growth and appearance of new tissues with greater nutritive value. Vendramini et al (2011) observed that annual ryegrass pastures grazed by early weaned calves receiving greater levels of RUP had greater HM and HA. The greater HM and HA observed was attributed to decreased FDMI of the calves receiving greater RUP supplementation levels.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, the replacement of sources of RDP by RUP may cause a depression of 7% on passage of microbial protein to the small intestine and the SBMSP treatment may have supplied a balanced amount of nonammonia nonmicrobial N and microbial protein. Vendramini et al (2011) tested the effects of increasing levels of RUP on FDMI, TDMI, and ADMD of calves receiving annual ryegrass. In the first year of the trial, there was no effect of the treatments on FDMI, TDMI, and ADMD; however, there was a significant decrease in FDMI and TDMI in the second year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation